Comparison of Two Dosing Regimens of Intravaginal Misoporostol for Second-trimester Abortion - Marzieh Ghasemi; Taraneh Arbabzadeh; Zohreh Baradaran; Fatemeh Sarvi (Mashhad University of Medical Sciences, 2018)
Introduction: Globally,second-trimester abortion accounts for 10-15% of all abortions and is responsible for two-thirds of abortion-related complications. Misoprostol is known as a powerful and effective medication for the termination of pregnancy in the second trimester. Several studies with different results were carried out into the proper dosage of misoprostol; however, there is no consensus about its proper dosage. This study was performed to compare the efficacy of two doses of vaginal misoprostol for second-trimester abortion. Methods: This randomized clinical trial was conducted among 100 pregnant women, who were hospitalized for second-trimester abortion. They were randomly assigned into two groups in the Department of Obstetrics and Gynecology, Ali ibn Abi Talib Hospital, Zahedan, Iran, 2013. The subjects in the first and second groups received vaginal misoprostol in the doses of 400 µg given every 3 hours and 600 µg given every 6 hours up to five doses, respectively. Data were collected using a form containing the received dose, abortion interval, and complications. Data analysis performed using Chi-squared and t-test. P<0.05 was considered statistically significant. Results: The mean age of participants was 58.5±5.5 years old; and all the abortions were successful. In the first group, total administered dose was significantly lower than the other group (P<0.001). Additionally, in the first group, the complications and abortion intervals were less than other group; nevertheless, there was no significant difference between them (P=0.108). Conclusion: Both studied doses of misoprostol had similar effects and the rate of complication was the same. Nonetheless, the dose of 400 µg was preferred due to need to lower total dose and shorter abortion interval.